Penanganan Kendaraan Bermotor Pada Kapal Angkutan Penyeberangan - Karana, Sjafril (Warta Penelitian Perhubungan, 2010)
Freight fernJ fleet has an important roe in launching the economic wheel. For that reason, the level of.ship safety would need to be nuzintnined. But in recent years are still often the case calamihJ befallingthe fernJ fleet. In accordance with kind of descripti'ue, this study prauides a clearer picture about thehandling of motor vehicle in the fleet of fernJ transport. Prinuzn1 dntn and infomuztian obtained underdirect obseniation to the boot fernJ transport.Tiiere are Parious factors thnt become the azuse of tlze accident or fire on board of the fernJ transport,including handling of ziehicles that are transported on the ship does not comply with regulations. It isslumm that the placement of motor ziehicles an fern/s deck is not yet unorganized. Space around theramp door location should be clear, but it was still loaded with drums, tliere is also a ramp door thatshould be tight closed, but now it was still slumm space wide enoughTiiere fore, to en[umce the safety of ships in their operation, niles enforcement needs to be appliedstrictly, it's tinie to apply las/zing system on each fem; in any condition. In addition, to ensure tlieenforcement of mies, supennsian needs to be clone on a regulnr basis and application of severe sanctionsis one of tlie effort tluit need to be applied, eitlier before tlie process of loading a vehicle or at tlietinie of sailing ships. So that any incident tluit occurs primarily in tlie space of vehicle ca:n be detectedas early as -possible.Keywords : zielzicle handling - safety of ferry fleet